Enhancing K2S2O8 electrochemiluminescence based on silver nanoparticles and zinc metal–organic framework composite (AgNPs@ZnMOF) for the determination of l-cysteine. Issue 36 (17th August 2022) - Wang, Lina; Wu, Qi; Yu, Ru; Zhang, Hongge; Nie, Fei; Zhang, Wenyan
Abstract : A silver nanoparticle-doped Zn(ii ) metal–organic framework composite (AgNPs@ZnMOF) was investigated as an electrochemiluminescence (ECL) signal enhancer for potassium persulfate. Abstract : A silver nanoparticle-doped Zn(ii ) metal–organic framework composite (AgNPs@ZnMOF) was investigated as an electrochemiluminescence (ECL) signal enhancer for potassium persulfate. First, ZnMOF was prepared by a one-step hydrothermal method, and then AgNPs@ZnMOF composite was obtained by depositing AgNPs on the surface and interior of ZnMOF. After the AgNPs@ZnMOF composite was modified on the glass carbon electrode (GCE), the cathode luminescence of potassium persulfate on bare GCE was enhanced by 8 times. A dual amplification mechanism provided by Zn(ii ) and Ag nanoparticles in the AgNPs@ZnMOF composite has been validated by ECL spectra, fluorescence spectra, and electrochemical methods. The interaction between the sulfhydryl groups in l -cysteine (l -Cys) and AgNPs significantly affects the catalytic luminescence of the AgNPs@ZnMOF composite. Thus, a sensitive ECL method for the determination of l -Cys was developed based on the inhibition effect of l -Cys on the ECL signal within the linear range from 5.0 nM to 1.0 μM and the limit of detection was found to be 2 nM (S/N = 3). The established method has been successfully applied to the determination of l -Cys in human urine.